Early Predictors of the Increase in Perihematomal Edema Volume After Intracerebral Hemorrhage: A Retrospective Analysis From the Risa-MIS-ICH Study - Ye, Gengzhao; Huang, Shuna; Chen, Renlong; Zheng, Yan; Huang, Wei; Gao, Zhuyu; Cai, Lueming; Zhao, Mingpei; Ma, Ke; He, Qiu; Lin, Fuxin; Lin, Yuanxiang; et al. (Frontiers in Neurology, 2021)
Background and Purpose: More and more attention has been paid to the effect of perihematomal edema (PHE) after intracerebral hemorrhage (ICH). PHE progresses fastest in the first 2-3 days, early identification of risk factors associated with PHE growth may allow for targeted therapeutic interventions. Methods: We used data contained in the Risa-MIS-ICH study (Risk stratification and minimally invasive surgery in acute intracerebral hemorrhage patients: a prospective multicenter cohort study). Patients' clinical, laboratory and radiological data within 24 hours of admission were obtained from their medical records. The absolute increase in PHE volume from baseline to day 3 was defined as iPHE volume. Poor outcome was defined as modified Rankin Scale (mRS) of 4 to 6 at 90 days. Binary logistic regression was used to assess the relationship between iPHE volume and poor outcome. The receiver operating characteristic (ROC) curve was used to find the best cut-off. Linear regression was used to identify variables associated with iPHE volume. ClinicalTrials.gov Identifier: NCT03862729 Results: 197 patients were included in this study. iPHE volume was significantly associated with poor outcome [P = 0.003, odds ratio (OR) 1.049, 95% confidence interval (CI) 1.016-1.082] after adjustment for hematoma volume. The best cut-off point of iPHE volume was 7.98 mL, with a specificity of 71.4% and a sensitivity of 47.5%. Diabetes mellitus (P = 0.043, β = 7.66 95% CI 0.26-15.07), black hole sign (P = 0.002, β = 18.93 95% CI 6.84-31.02) and initial ICH volume (P = 0.018, β = 0.20 95% CI 0.03-0.37) were significantly associated with iPHE volume. Conclusions: An increase of PHE volume > 7.98 mL from baseline to day 3 may lead to poor outcome. Patients with diabetes mellitus, black hole sign and large initial hematoma volume will result in more PHE growth, which should be paid attention to in the treatment.